The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/5547274
|View full text |Cite
|
Sign up to set email alerts
|

Energy and Economic Analysis of Curved, Straight, and Spiral Flow Flat-Plate Solar Water Collector

Abstract: In this work, the solar water collector flow tube geometry is modified as curved and spiral to enhance the system’s performance. The investigation is carried out experimentally under the meteorological conditions of the Kovilpatti region (9°10 ′ 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The experimental study revealed that the treated heat pipes resulted in an 80% increase in the collector's thermal performance and a 44% reduction in the thermal resistance [160]. Muthuraman et al [161] in Tamil Nadu, India, experimented with three geometric configurations of the FPC's flow tubes: straight, curved, and spiral-shaped. They concluded that the spiral tube configuration yielded the best efficiencies of 69% and 73% for water mass flow rates of 0.0045 kg/s and 0.006 kg/s, respectively.…”
Section: Solar Water Heater Performance Enhancement Methodsmentioning
confidence: 99%
“…The experimental study revealed that the treated heat pipes resulted in an 80% increase in the collector's thermal performance and a 44% reduction in the thermal resistance [160]. Muthuraman et al [161] in Tamil Nadu, India, experimented with three geometric configurations of the FPC's flow tubes: straight, curved, and spiral-shaped. They concluded that the spiral tube configuration yielded the best efficiencies of 69% and 73% for water mass flow rates of 0.0045 kg/s and 0.006 kg/s, respectively.…”
Section: Solar Water Heater Performance Enhancement Methodsmentioning
confidence: 99%
“…Every hour from the commencement of 8 a.m. to the completion of the examination at 6 p.m., temperature data were recorded using 11 J-type temperature sensors and a digital recorder. Hourly measurements of solar irradiance and generated clean water had been also made with an electronic solar metre and a metered container [26,27]. The thermodynamic effectiveness the solar stills was tested in real environmental conditions at a fixed water depth of 2.0 cm.…”
Section: Methodsmentioning
confidence: 99%
“…For the processing of discontinuous rein-forced AMCs, several researchers prefer to employ stir casting route. e foremost objective of melt stirring is that it is trouble-free, flexible, unproblematic, reasonable, and appropriate for bulk production [16,17]. Mohanavel et al [18] utilized melt stirring to manufacture AA6351/SiC AMCs.…”
Section: Stir Castingmentioning
confidence: 99%